Examination of trust and sustainability concerns in autonomous vehicle adoption - DİRSEHAN, TAŞKIN (ELSEVIER SCI LTD, 2020)
The latest developments regarding autonomous vehicles (AVs) have drawn the attention of tech-savvy individuals and marketers. AVs are expected to cause a major change in the markets of vehicle selling, transportation and logistics. Therefore, it is crucial to understand consumer acceptance so that the companies in these markets can develop their penetration strategies accordingly and technology companies can shape their technology development strategies. This study aims to examine individuals' adoption attitudes toward AVs by considering trust and sustainability concerns. This was achieved by expanding the technology acceptance model (TAM). A survey of 391 participants was conducted and the data were analyzed using structural equation modeling (SEM). The results confirmed previous technology acceptance models by showing the relationships between perceived usefulness, perceived ease of use, and behavioral intention. Moreover, the direct and indirect effects of trust on behavioral intention were also shown. This study provides evidence to extend the TAM to the adoption of AVs by uncovering individuals' sustainability concerns.
Keywords: Autonomous vehicles; Technology acceptance modelling; Sustainability; Trust in automation; TECHNOLOGY ACCEPTANCE MODEL; USER ACCEPTANCE; PERCEIVED RISK; INFORMATION-TECHNOLOGY; CONSUMER ACCEPTANCE; AUTOMATION; BEHAVIOR; INNOVATION; SERVICES; SYSTEM